2001
DOI: 10.1148/radiographics.21.5.g01se311155
|View full text |Cite
|
Sign up to set email alerts
|

CT Evaluation of Cervical Cancer: Spectrum of Disease

Abstract: Invasive cervical cancer is the third most common gynecologic malignancy. The prognosis is based on the stage, size, and histologic grade of the primary tumor and the status of the lymph nodes. Assessment of the stage of disease is important in determining whether the patient may benefit from surgery or will receive radiation therapy. The official clinical staging system of the International Federation of Gynecology and Obstetrics has led to errors of 65%-90% in stage III and IV disease; the result has been un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(41 citation statements)
references
References 28 publications
0
40
0
1
Order By: Relevance
“…The response may be immediate (3-6 months) or, in larger tumors, delayed (6-9 months) [15]. Hricak et al reviewed the MR images of 69 patients submitted to radiotherapy to cervical cancer and reported that the reconstitution of the normal zonal anatomy of the cervix and homogeneous cervical low signal have high negative predictive value (97%) for recurrence [14].…”
Section: Normal Post-therapeutical Imaging Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…The response may be immediate (3-6 months) or, in larger tumors, delayed (6-9 months) [15]. Hricak et al reviewed the MR images of 69 patients submitted to radiotherapy to cervical cancer and reported that the reconstitution of the normal zonal anatomy of the cervix and homogeneous cervical low signal have high negative predictive value (97%) for recurrence [14].…”
Section: Normal Post-therapeutical Imaging Findingsmentioning
confidence: 99%
“…Adrenal metastases are usually from cervical adenocarcinomas and are present in approximately 15% of patients. Peritoneal metastases appear as soft-tissue masses and ascites and are present in 5%-27% of cases in autopsy series (Figure 14) [15,28].…”
Section: Distant Recurrent Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Prognoses of cervical cancer are based on the stage, size, histologic grade of a primary tumor and metastasis of lymph node. 3 Most of metastasis begins in the surround lymph node, and common distant metastatic sites of cervical cancer are lung, gastrointestinal tract, bone, and liver. 3 Distant metastases can be rarely developed in skin and central nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…3 Most of metastasis begins in the surround lymph node, and common distant metastatic sites of cervical cancer are lung, gastrointestinal tract, bone, and liver. 3 Distant metastases can be rarely developed in skin and central nervous system. 4,5 CT and MRI are useful in staging advanced disease and in monitoring patients for recurrence of the disease.…”
Section: Introductionmentioning
confidence: 99%